(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines methodological approaches to developing reading skills in primary school learners. The components of reading proficiency—reading fluency, conscious reading, expressive reading, text comprehension, and retelling—are analyzed from a scientific perspective. The effectiveness of phonetic exercises, text-based instruction, differentiated tasks, and interactive learning strategies in improving reading literacy is demonstrated. Considering the developmental and psychological characteristics of young learners, the paper proposes a step-by-step model for forming strong reading skills in primary education.